Correlation of Pain Intensity and Pain Interference in Post Operation Patients - Ice Septriani Saragih; Ernita Rante Rupang; Lindawati Tampubolon; Amnita Anda Yanti Ginting; Lindawati Simorangkir (Indonesian Journal of Global Health Research, 2022)
Surgery is all treatment measures that use invasive methods by opening or displaying the body part to be treated. The most frequent and common problem caused postoperatively is pain Objective: The aim of this study was to determine the correlation of pain intensity and pain interference in postoperative patients Method: Desaign of This research is a descriptive correlative research using a cross sectional design. The number of samples in this study were 70 people. The sampling technique used is accidental sampling. Bivariate analysis used is the product moment test. Results: The results showed that postoperative patients had severe pain intensity with a total of 44 people and a percentage of 62.90%, had moderate pain interference with a total of 49 people and a percentage of 70 and there was a significant relationship between pain intensity and pain interference in postoperative patients (p value =0.001, <0.005). Conclusions The conclusion of this study is there was a significant relationship between pain intensity and pain interference in postoperative patients